PENGARUH QUALITY OF WORK LIFE TERHADAP KEPUASAN KERJA DOSEN - Wahyuningsih, Nining (Holistik: Journal for Islamic Social Sciences, 2016)
One of the problems facing the organization is the low quality of human resources. Number of human resources greater if properly empowered and effectively will give an advantage in achieving organizational goals. Organizational goals will be achieved when employees merndapat satisfaction in work. In creating human resources capable of competing on the rapid changes in the human resources needs to be fostered by the Quality of Work Life. Quality. Components of the Quality of Life work consists of participation of employees, career development, conflict resolution, communication, health, safety, health, work environment, adequate compensation and a sense of pride. Job satisfaction is the general attitude of workers who assess the difference between the amount that should he get by the number obtained. Formulation of the problem in this research are: 1) is there any influence of Quality of Work Life on job satisfaction Lecturer at the Faculty of Sharia and Islamic Economics IAIN Sheikh Nurjati Cirebon.2) What Factors Quality of Work Life the dominant influence on job satisfaction Lecturer at the Faculty of Sharia Economic and Islam IAIN Sheikh Nurjati Cirebon. The data used is data Quantitative and methods of research using descriptive method. Data collection techniques in this study using a standard scale questionnaire using Likert scale. Test Multiple Linear Regression Y = 35.654 + 0.751 X2 + 0,926X6 variables that most affect job satisfaction lecturers are working environment with a coefficient of 0.926, the second variable that affects job satisfaction is career development with a coefficient of 0.751 Adjusted R Square figures or coefficient of determination of 0.421 means a variation of job satisfaction can be explained by the variable QWL From ANOVA or F test, obtained F count was 16.295 with a significance level of 0.000 for 0.000 probability less than 0.05, the regression model can be used to predict job satisfaction or work environment and development career together Lecturer effect on job satisfaction.Â Keywords: Quality of Work Life, Job SatisfactionÂ